Internalisasi Nilai PAI melalui Deep Learning untuk Meningkatkan Kolaborasi Anak Usia Dini di RA Zainal Ali - Nailul Muchliso; Muhammad Nur Hadi; Muhammadah; Saifulah (Ta’dib : Jurnal Pendidikan Islam, 2026)
This study aims to describe the internalization of Islamic Religious Education values through deep learning to improve early childhood collaboration at RA Zainal Ali Karangasem Wonorejo Pasuruan. This research employed a phenomenological qualitative method, using observation, interviews, and documentation as data collection techniques, with data analyzed through reduction, presentation, and verification. The findings indicate that deep learning encourages active engagement, meaningful understanding, and the habituation of values such as cooperation, responsibility, and empathy. Children demonstrated improved collaborative behavior, including sharing, waiting for their turn, and helping their peers. These findings confirm that this approach is effective in integrating cognitive, affective, and social aspects into Islamic Religious Education learning. The implication is that teachers need to design contextual, collaborative, and reflective activities so that religious values can be consistently internalized in children’s daily practices while supporting the development of twenty-first-century skills from an early age. Parental involvement also strengthens the continuity of value habituation.